Landscape Design and Drawing in The Draughtsman’s Contract: Peepholes to an Age - Chantal Cornut-Gentille D'Arcy (Miscelánea: A Journal of English and American Studies, 1993)
The basic plot in Peter Greenaway’s The Draughtsman’s Contract is no more and no less than an ingeniously planned murder and its dramatic consequences for a guest artist. However, the views of Mr. Herbert’s house and property, which the draughtsman is commissioned to reproduce on paper, do not serve merely as a background setting for the story. Close attention to the mise-en-scene, to remarks made by characters about gardens, garden elements or garden produce and to the artist’s work-technique reveal how much the insight into the times in The Draughtsman’s Contract accords to the period, while it also provides interesting clues that help the viewer elucidate several, otherwise, obscure or baffling scenes.